Milking management practices followed by dairy farmers in tribal areas of Valsad district of Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in Valsad district of Gujarat to ascertain the milking management practices  followed by dairy animal owners and data were collected from randomly selected 240 dairy animal farmers  through personal interview with the help of structured interview schedule. The present study revealed that  all the respondents milked their animals twice a day at same place and practiced washing of teats and  udder of animals as well as their hands before milking. About 96.2 and 81.7% respondents were adopted  wet hand milking and knuckling method of hand milking, respectively. Only 27.9% of respondents followed  stripping at the end of milking and all the respondents didn’t wipe the udder and teats just after milking.  Majority (72%) of respondents change the milker for their milking animals. About 44.2% of respondents  allowed calves for suckling before milking and 80% of respondents washed their milking utensils by  simply tap water. Majority (90.8%) of respondents did not follow teat dipping after milking and none of the  respondents followed testing for mastitis in their dairy animals. Only 38.82% respondents adopted practice  of drying off their dairy animals for less than two months before calving. Majority (99.6%) of respondents  didn’t follow sealing of teat canal at the end of lactation. Majority (98.3%) of respondents sold their milk  to village dairy co-operative society.
Keywords: Dairy animals; Milking; Management; Practices; Tribal area